2013
DOI: 10.1523/jneurosci.5606-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Deletion of Atoh1 Reveals Distinct Critical Periods for Survival and Function of Hair Cells in the Organ of Corti

Abstract: Atonal homolog1 (Atoh1) encodes a basic helix-loop-helix protein that is the first transcription factor to be expressed in differentiating hair cells. Previous work suggests that expression of Atoh1 in prosensory precursors is necessary for the differentiation and survival of hair cells, but it is not clear whether Atoh1 is required exclusively for these processes, or whether it regulates other functions later during hair cell maturation. We used EGFP-tagged Atoh1 knock-in mice to demonstrate for the first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
149
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(159 citation statements)
references
References 49 publications
(3 reference statements)
10
149
0
Order By: Relevance
“…Furthermore, Lgr5 acts as a receptor for R-spondins. At postnatal stages, addition of Rspo1 to dissociated Lgr5-expressing cochlear cells induces expression of hair cell markers (Chai et al, 2012;Shi et al, 2012), and we show that addition of Rspo1 to embryonic cochleae leads to an increase in hair cells. This implies that the Lgr5-positive cells respond to stimulation with the Wnt potentiator, Rspo1, during development.…”
Section: ␤-Catenin Is Required For Cell Patterning In Developing Orgasupporting
confidence: 62%
See 3 more Smart Citations
“…Furthermore, Lgr5 acts as a receptor for R-spondins. At postnatal stages, addition of Rspo1 to dissociated Lgr5-expressing cochlear cells induces expression of hair cell markers (Chai et al, 2012;Shi et al, 2012), and we show that addition of Rspo1 to embryonic cochleae leads to an increase in hair cells. This implies that the Lgr5-positive cells respond to stimulation with the Wnt potentiator, Rspo1, during development.…”
Section: ␤-Catenin Is Required For Cell Patterning In Developing Orgasupporting
confidence: 62%
“…Using similar reporters based on multimerized TCF sites upstream of other promoters, TOP-gal and TCF/LEF:H2B-GFP, we and others have found that Wnt activity parallels the course of hair-cell development (DasGupta and Fuchs, 1999;Jacques et al, 2012;Shi et al, 2013). Lgr5-GFP, a downstream Wnt target gene which successfully identified Wnt-responsive stem cells in intestine (Barker et al, 2007), reveals a similar pattern of Wnt activity in the developing cochlea (Chai et al, 2012;Shi et al, 2012).…”
Section: Canonical Wnt Activity In the Developing Cochleamentioning
confidence: 99%
See 2 more Smart Citations
“…Atoh1, a transcription factor belonging to the family of basic helix-loop-helix (bHLH)-containing proteins, plays a critical role for hair cell differentiation and survival during development and adulthood [15,17,18]. The Atoh1 -CKO mouse self-terminates expression of Atoh1 in hair cells around birth using an Atoh1 enhancer to drive cre to conditionally delete the floxed Atoh1 .…”
Section: Introductionmentioning
confidence: 99%